2015
DOI: 10.1007/s00228-015-1988-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of commercial Rhodiola rosea on CYP enzyme activity in humans

Abstract: This study indicates that R. rosea inhibits the metabolic capacity of CYP2C9 in humans. Although the effect is modest, it might be clinically relevant during treatment with CYP2C9 substrates with a narrow therapeutic index, such as phenytoin and warfarin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Opposed to this, the study by Spanakis et al (2013), showed a significant inhibition in the metabolism of losartan [CYP3A4, CYP2C9 and CYP2C10 substrate (Sica et al 2005)] in rabbits after oral administration of a R. rosea product. Just recently, we found a 23% reduction in CYP2C9 activity in a cross-over study (including 13 human males) with the commercial R. rosea product Artic Root (Thu et al 2016). To our knowledge, no studies have been published comparing inhibitory potential between different commercial R. rosea products.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Opposed to this, the study by Spanakis et al (2013), showed a significant inhibition in the metabolism of losartan [CYP3A4, CYP2C9 and CYP2C10 substrate (Sica et al 2005)] in rabbits after oral administration of a R. rosea product. Just recently, we found a 23% reduction in CYP2C9 activity in a cross-over study (including 13 human males) with the commercial R. rosea product Artic Root (Thu et al 2016). To our knowledge, no studies have been published comparing inhibitory potential between different commercial R. rosea products.…”
Section: Introductionmentioning
confidence: 83%
“…Five studies have previously been published on CYP inhibition by full extracts of R. rosea (Scott et al 2006;Panossian et al 2009;Hellum et al 2010;Spanakis et al 2013;Thu et al 2016). Hellum et al (2010) showed that ethanol extracts of R. rosea clones (raw plant material) significantly inhibited CYP3A4 in vitro, with IC 50 values ranging from 1.7-3.1 lg/mL.…”
Section: Introductionmentioning
confidence: 99%
“…It may be clinically relevant during concomitant use of Rhodiola rosea extract and CYP2C9 substrates with a narrow therapeutic index (e.g., phenytoin and warfarin). A full pharmacokinetic study with these substrates should be conducted to confirm and extend the results from Thu et al's study [40]. …”
Section: Resultsmentioning
confidence: 82%
“…Phenotyping cocktail approach indicated that pretreatment with Rhodiola rosea extract 290 mg daily for 14 days could reduce CYP2C9 activity by 21% without significant effects on CYP1A2, CYP2C19, CYP2D6, and CYP3A4 [40]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation